Saying it with music: a theoretical exploration of musical encoding with reference to Western art music and the songs of the Ngqoko women - Jankowitz, Christo (My University, 2012)
This research-report presents a theoretical exploration of musical encoding which has its basis in general semiotic theory. By examining what this reveals about the problematic and mysterious issue of music’s meaning, I argue that the most visceral and direct form of it is found in the manner in which the composer shapes a certain kind of temporal experience (erlebnis) which is engendered by the music itself. This reveals that sensations of goal-directed movement, closure, tension and release are shaped in a phenomenological way against a background of continuity that is established by metrical cyclicity and phrasal periodisation. As a result, the interpretation of certain kinds of accumulative structural effects generated by the gestural (rhythmic and melodic/harmonic) inflections of the temporal and intonational planes become meaningful in a rhetorical, affective (affekten) and topical sense. A study of Ngqoko (Xhosa) overtone-music, as a case study into African indigenous music (as opposed to the examples cited of Western art music), shows that an intensification of the relationships between pitch and rhythm that exist in speech-tone results in the formation of melody and a culturally embedded vocabulary of intonations. I argue that this resultant edifice exists in the music of most cultures and that this ultimately serves as the basis of musical encoding. Therefore musical meaning develops in ways that are completely intrinsic to music.
MA, Faculty of Humanities, University of the Witwatersrand, 2012
Keywords: encoding; gesture theory; intonation; musical codes; music and language; overtone-singing; Ngqoko Women's Ensemble; pre-linguistic speech; rhetoric; semantics; semiotics; speech-tone; speech-tone melody; temporal theory; topical theory; Xhosa music